1991
DOI: 10.1111/j.1468-3156.1991.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff training in the management of violence and aggression: 1 – SETTING UP A TRAINING SYSTEM

Abstract: This article, the first in a three‐part series, discusses staff training in the management of violence and aggression. It begins by examining the setting conditions required to set up a training course. Training is placed in the context of an organisational system. A most crucial factor in the successful outcome of training is the provision of clear, precise policies and guidelines. The remainder of the article discusses some useful specifications within these policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…37 Interestingly it has been suggested that training can aid staff coping responses. 38 The importance of engaging the support of care home managers in implementing the training is in keeping with previous studies considering educational interventions in this setting. 39 Our findings regarding falls prevention usual care are in keeping with existing literature, which suggest this to be predominantly ad hoc and reactive.…”
Section: Discussionmentioning
confidence: 59%
“…37 Interestingly it has been suggested that training can aid staff coping responses. 38 The importance of engaging the support of care home managers in implementing the training is in keeping with previous studies considering educational interventions in this setting. 39 Our findings regarding falls prevention usual care are in keeping with existing literature, which suggest this to be predominantly ad hoc and reactive.…”
Section: Discussionmentioning
confidence: 59%